Functional and radiological comparison of transforaminal lumbar interbody fusion method with interbody fusion device versus stand-alone bone graft in lumbar canal stenosis or degenerative lumbar instability - Gupta, Ashish Kumar; Rathore, Jitendra Singh; Bhati, Lokpal Singh; Rathore, Devendra Singh; Meena, R. C. (International Journal of Research in Orthopaedics, 2021)
Background: Spinal stability is the vertebral ability to maintain their relationship and limit their relative displacements during physiologic postures and loads. Methods: Hospital based prospective randomized comparative study design between 2 groups included patients of both sex attending SMS hospital Jaipur, from April 2018 to June 2019 or till sample size was achieved, with due permission from institutional ethical committee and review board and after taking written informed consent from patients. Results: Inter group comparison of VAS score showed same results in both groups which showed statistically non-significant results. VAS score showed significantly reduction in both group A and B till the study period. Inter group comparison of ODI score showed same results in both groups which showed statistically non-significant results. ODI score showed significantly reduction in both group A and B till the study period. Inter group comparison of fusion rate score showed same results in both groups which showed statistically non-significant results. Fusion rate score showed significantly increased in both group A and B till the study period and at the 12 month it was 100% fusion rate. Conclusions: In the current series, the TLIF procedure with local bone graft alone improved anterior vertebral translation, disc height, and lumbar lordosis. A proper surgical technique with adequate discectomy and facetectomy would contribute greatly to the improvement of the radiological parameters; however, this improvement was not maintained at the latest follow up.